SUMBER DAYA MANUSIA PEMRINTAH DESA DALAM PENGELOLAAN DANA DESA - Mahyudin Mahyudin; L.M. Fakhri Mihzan; Asrin Asrin; Nurlinda Nurlinda (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2022)
The authority of the village government to manage such a large amount of funds independently carries a heavy responsibility. For this reason, quality human resources are needed, so that the village government can manage funds based on the principles of good governance. This study aims to analyze the quality of human resources in the District Government of South Lasalimu, Buton Regency. This study uses a qualitative methodology and uses interviews as a method of collecting data. To measure the quality of human resources, this study took indicators of knowledge, skills, abilities and experience. The results showed that based on the four indicators of the quality of human resources, the Village Government of Lasalimu Selatan District was still inadequate to manage village funds. There needs to be an effort from the local government to improve the quality of the human resources of the village government.Kewenangan pemerintah desa untuk mengelola dana sebesar itu secara mandiri memiliki tanggung jawab yang berat. Untuk itu diperlukan sumber daya manusia yang berkualitas, sehingga pemerintah desa dapat mengelola dana berdasarkan prinsip tata kelola pemerintahan yang baik. Penelitian ini bertujuan untuk menganalisis kualitas sumber daya manusia pada Pemerintah Kecamatan Lasalimu Selatan Kabupaten Buton. Penelitian ini menggunakan metodologi kualitatif dan menggunakan wawancara sebagai metode pengumpulan datanya. Untuk mengukur kualitas sumber daya manusia, penelitian ini mengambil indikator pengetahuan, keterampilan, kemampuan dan pengalaman. Hasil penelitian menunjukkan bahwa berdasarkan keempat indikator kualitas sumber daya manusia Pemerintah Desa Kecamatan Lasalimu Selatan masih belum memadai untuk mengelola dana desa. Perlu ada upaya dari pemerintah daerah untuk meningkatkan kualitas sumber daya manusia pemerintah desa.